Preparation and Evaluation of Celecoxib Polysaccharide Based Matrix Tablets Using NanoParticular Approach - Bhattacharya, Sankha (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: Celecoxib has a tremendous role in the treatment of colon polyps and Crohn’s disease. However, gastric resistant has always been an issue for drug delivery to the colon. Our main intention of this experiment was to prepare and evaluate a formula which could resist gastrointestinal fluid and releases drug content not more than 10% within simulated gastric fluid for 2 h from the time of administration. Materials and Methods: In this experiment at first, we prepared Celecoxib nanoparticles using Dyno Mill taking Acconon MC8-2EP as a surfactant and Capmul MCM L-8 as cosurfactant. Freshly prepared Celecoxib nanoparticles were then admixed with Lactopress® anhydrous and using dry granulation technique 10 batches of Celecoxib tablets were formulated by altering various ratios of resistant starch, dextran, and gellan gum. Tablets were prepared using dry granulation technique, where ALTRIN® was considered as a principal binder. Results and Discussion: All the pre and post compression parameters were evaluated, and it was found that D-3 batch has legitimate cumulative percentage dissolution profile up to a 24th h (98.12%). Furthermore, similarity and dissimilarity studies were performed against Ortho bed tablet (marketed) and the test optimized formula D-3. The similarity factor (F2) and difference or dissimilarity factors (F1) were found to be 60.90 and 10.16, respectively, which is within the specified limits. Finally, as per ICH guideline Q1A (R2) at 40°C ± 2°C/75% RH ± 5% RH accelerated stability studies was performed in the D-3 formulation for 6 months. Stability results were quite satisfactory. Conclusion: Hence, it can be concluded that the optimized D-3 batch can be conceded for the pilot scalp.